PPM Pengrajin Panci Kampung Lajuk Porong Sidoarjo - Muharom Muharom; Krisnadi Hariyanto; Siswadi Siswadi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
UMKM Porong "Lajuk" Pot Craftsmen are located in Lajuk Village, Porong District, Sidoarjo Regency. This lajuk village has an average population of livelihoods as craftsmen. Until now, the partner had several problems that hindered the development of his business, including the production aspect, namely the process of giving a hole to the pan which often misses from the desired point or even the pan hole is too large so that it cannot be used to stick the pan handle. Aspects of management, partners do not have a proper marketing plan and do not have financial records so that it hinders any decisions in developing a business. Solutions in solving the problem are: 1) Designing a TTG (Appropriate Technology) machine design to make a pan hole by identifying the size of the pan hole so that the machine matches what the partner wants. 2) Provide training and mentoring by conducting discussions, interviews, and determining actual marketing problems, 3) Providing training and assistance in making financial reports and providing materials according to needs. The output target of this solution is to produce a machine design to perforate the pan as needed, have a marketing plan, and have a detailed financial report according to the partner's pan business conditions.